2010
DOI: 10.1111/j.1537-2995.2009.02535.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprecipitate prepared from plasma frozen within 24 hours after phlebotomy contains acceptable levels of fibrinogen and VIIIC

Abstract: All units of cryo24 in this pilot study met the current minimum content standards for cryo. While clinical studies of its efficacy are warranted, cryo24's in vitro characteristics are at least equivalent to that of standard cryo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Cryoprecipitate is a concentrated form of fibrinogen derived from plasma. It is administered in pools of 4 to 6 units, with the total amount of fibrinogen per pool typically approaching 2000 mg in approximately 100 mL of plasma . There is approximately 700 mg of fibrinogen in a unit of plasma, assuming there is approximately 3 mg/mL of fibrinogen in a 230‐mL plasma unit, so the number of doses of cryoprecipitate can be adjusted based on the number of plasma units transfused .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryoprecipitate is a concentrated form of fibrinogen derived from plasma. It is administered in pools of 4 to 6 units, with the total amount of fibrinogen per pool typically approaching 2000 mg in approximately 100 mL of plasma . There is approximately 700 mg of fibrinogen in a unit of plasma, assuming there is approximately 3 mg/mL of fibrinogen in a 230‐mL plasma unit, so the number of doses of cryoprecipitate can be adjusted based on the number of plasma units transfused .…”
Section: Discussionmentioning
confidence: 99%
“…It is administered in pools of 4 to 6 units, with the total amount of fibrinogen per pool typically approaching 2000 mg in approximately 100 mL of plasma. 31 There is approximately 700 mg of fibrinogen in a unit of plasma, assuming there is approximately 3 mg/mL of fibrinogen in a 230-mL plasma unit, so the number of doses of cryoprecipitate can be adjusted based on the number of plasma units transfused. 20 Cryoprecipitate should be transfused when a trauma patientʼs fibrinogen concentration is <150 to 200 mg/dL and fibrinogen supplementation is required beyond what is provided in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Cryoprecipitate contains a higher concentration of fibrinogen than FFP, typically around 15 g/L. 11,12 However, it shares many of the disadvantages of FFP. The risk of viral transmission is similar to that with FFP, but the risk is enhanced by the fact that each pool of cryoprecipitate contains human plasma from multiple donors.…”
Section: Cryoprecipitatementioning
confidence: 99%
“…Other studies have demonstrated that CryoAHF manufactured from PF24 yields an acceptable product per AABB standards 5 . Canadian Blood Services (CBS) manufactures cryoprecipitated fibrinogen concentrate (CFC) from the buffy coat method, allowing blood to be held overnight prior to separation and freezing the plasma within 24 h 6 .…”
Section: Introductionmentioning
confidence: 99%